O IFMS DE TRÊS LAGOAS/MS E A (RE) CONFIGURAÇÃO DOS CURSOS TÉCNICOS NO BRASIL - Renata Moreira Delgado (2021)
This dissertation has as its object of analysis the Federal Institute of Mato Grosso do Sul (IFMS) campus of Três Lagoas – MS. The main objective of the research is to understand the (re) configuration of technical courses in Brazil in recent decades from the restructuring of the capitalist mode of production. Therefore, the technical/professional education offered by the IFMS campus Três Lagoas was chosen as investigation. It is theoretically based on authors such as Mézáros (2002, 2008), Fernandes (1975, 2020), Antunes (2009, 2015, 2017), Frigotto (1993, 2003, 2006, 2018), Frigotto and Ciavatta (2003, 2005) and Saviani (2018) and is anchored in the dialectical historical materialist method in an attempt to unveil the concrete reality of the teaching process and the professional and technological training of this institution. The work has a qualitative approach with document analysis of official documents related to the offer of professional and technological education in Brazil and official documents from the IFMS, as well as the pedagogical education in Brazil and official documents from the IFMS, as well as the pedagogical projects of the secondary level technical courses offered by the Três Lagoas campus. The results demonstrate that the IFMS Três Lagoas, within the larger program, is structured to serve the capital´s corporate project, offering a functional education to the system. However, they also demonstrate that the institution is or can become an emancipatory project, in the sense of polytechnics, since it develops activities towards the universalization of education. The IFMS/TL can contribute to the process of building polytechnic education and human emancipation, as a formal institution of professional and technological education.